The 2021 Updated European Association of Urology Guidelines on Metastatic Urothelial Carcinoma - Cathomas, Richard; Lorch, Anja; Bruins, Harman M.; Compérat, Eva M.; Cowan, Nigel C.; Efstathiou, Jason A.; Fietkau, Rainer; Gakis, Georgios; Hernández, Virginia; Espinós, Estefania Linares; Neuzillet, Yann; Ribal, Maria J.; et al. (European Urology, 2022)
Context: Treatment of metastatic urothelial carcinoma is currently undergoing a rapid evolution. Objective: This overview presents the updated European Association of Urology (EAU) guidelines for metastatic urothelial carcinoma. Evidence acquisition: A comprehensive scoping exercise covering the topic of metastatic urothelial carcinoma is performed annually by the Guidelines Panel. Databases covered by the search included Medline, EMBASE, and the Cochrane Libraries, resulting in yearly guideline updates. Evidence synthesis: Platinum-based chemotherapy is the recommended first-line standard therapy for all patients fit to receive either cisplatin or carboplatin. Patients positive for programmed death ligand 1 (PD-L1) and ineligible for cisplatin may receive immunotherapy (atezolizumab or pembrolizumab). In case of nonprogressive disease on platinum-based chemotherapy, subsequent maintenance immunotherapy (avelumab) is recommended. For patients without maintenance therapy, the recommended second-line regimen is immunotherapy (pembrolizumab). Later-line treatment has undergone recent advances: the antibody-drug conjugate enfortumab vedotin demonstrated improved overall survival and the fibroblast growth factor receptor (FGFR) inhibitor erdafitinib appears active in case of FGFR3 alterations. Conclusions: This 2021 update of the EAU guideline provides detailed and contemporary information on the treatment of metastatic urothelial carcinoma for incorporation into clinical practice. Patient summary: In recent years, several new treatment options have been introduced for patients with metastatic urothelial cancer (including bladder cancer and cancer of the upper urinary tract and urethra). These include immunotherapy and targeted treatments. This updated guideline informs clinicians and patients about optimal tailoring of treatment of affected patients.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Bladder cancer; European Association of Urology; Guidelines; Immunotherapy; Metastatic; Systemic therapy; Urothelial carcinoma